Single Presence Policy in Indonesian Banking - Muchtar, Andhyka; Widodo, Widodo; Habeahan, Rasman (PT FORMOSA CENDEKIA GLOBAL, 2024)
The sole ownership policy in Indonesian banking is regulated in Bank Indonesia Regulation Number 14/24/PBI/2012 concerning Sole Ownership in Indonesian banking which is then supplemented by Bank Indonesia Circular Letter Number 15/2/DPNP dated 4 February 2013 concerning Sole Ownership in Indonesian Banking. This research was created to find out about the regulations and implementation of sole ownership policies in banking in Indonesia. The research uses normative juridical research methods. The research results state that the implementation of the sole ownership policy in banking in Indonesia is carried out through the merger or consolidation of controlled banks, forming a Holding Company in the Banking Sector (Bank Holding Company/BHC), forming a Holding Function. There is a need for further study regarding the implementation of the sole ownership policy in banking in Indonesia.